FORMING THE JOURNALISTIC MINDSET AS THE KEY PARADIGM OF JOURNALISM EDUCATION – REVITALIZATION OF THE TRUTH IN THE SHADOW OF THE PROPAGANDA MODEL OF GLOBALISM - Petrović, Radivoje S (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
In recent decades, structural changes in journalism have imposed the need to redefine the academic education of journalists. One of the key paradigms in that process is the formation of journalistic mindset. This is the category of journalistic profession almost completely forgotten. In that sense, the new concept of education would go in two directions: professional and ideological. The first one, professional, would have the following: 1. Core standards of the profession 2. critical thinking and 3. development of research spirit, as the necessary components for the competent engagement in business. The ideological direction of journalistic way of thinking would have four important moments: 1. Eliminating the impact of dominant values of rich Western societies as a colonial ideology 2. Insisting on national, rather than foreign interests, 3. Employing the cultural model based on common traditions and values and 4. Changing the consciousness, and focusing on national rather than the colonial one. The aim of this approach to journalistic education is to institutionalize a solid basis for the development of healthy and democratic national consciousness, as an essential segment of journalistic profession, in terms of the impact and significance of media in society. This well-oriented professional way of thinking, would then help in creating the ideological, moral and professional basis for the formation of national aspect of democratic public, which in terms of the current absence of this component, results in inadequate presentation of ideas of national and democratic state.